Aromaticity and Other Conjugation Effects. Von Rolf Gleiter und Gebhard Haberhauer. (30th January 2013) - Scott, Lawrence T.; Cho, Hee Yeon; Eliseeva, Maria N.; Jackson, Edward A.; Tanaka, Takayuki; Tanikawa, Tomoharu
<x xml:space="preserve">Abstract</x> Wiley‐VCH, Weinheim, 2012. 452 S., geb., 129.00 €—ISBN 978‐3527329465 (Broschur, € 59.00.—ISBN 978‐3527329342)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>